2019
DOI: 10.17533/udea.iee.v37n2e04
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic fatigue in resuscitators using personal protection equipment against biological hazard

Abstract: Objective. To describe the effects of wearing individual protection equipment against biological hazard when performing a simulated resuscitation.Methods. Uncontrolled quasi-experimental study involving 47 volunteers chosen by random sampling stratified by sex and professional category. We determined vital signs, anthropometric parameters and baseline lactate levels; subsequently, the volunteers put on level D individual protection equipment against biological hazard and performed a simulated resuscitation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Many studies and experts have reported that the use of proper PPE for the medical staff can reduce the risk of infection for medical staff and patients ( 6 , 7 ). However, when medical staff conduct their work with the necessary PPE, these PPE directly affect the physiology of medical staff, since it generates significant metabolic fatigue ( 8 , 9 ). More importantly, this metabolic fatigue can not only impact operational capacity ( 10 ), but also increase the risk of accidents with PPE, increase cross-contamination, and contribute to physiological stress ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies and experts have reported that the use of proper PPE for the medical staff can reduce the risk of infection for medical staff and patients ( 6 , 7 ). However, when medical staff conduct their work with the necessary PPE, these PPE directly affect the physiology of medical staff, since it generates significant metabolic fatigue ( 8 , 9 ). More importantly, this metabolic fatigue can not only impact operational capacity ( 10 ), but also increase the risk of accidents with PPE, increase cross-contamination, and contribute to physiological stress ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when medical staff conduct their work with the necessary PPE, these PPE directly affect the physiology of medical staff, since it generates significant metabolic fatigue ( 8 , 9 ). More importantly, this metabolic fatigue can not only impact operational capacity ( 10 ), but also increase the risk of accidents with PPE, increase cross-contamination, and contribute to physiological stress ( 9 ). N95 masks, as an important PPE, have good filtration efficiency for small particles, but also hinder airflow.…”
Section: Introductionmentioning
confidence: 99%